Phthalocyanine-sulfonamide conjugates: synthesis and photodynamic inactivation of Gram-negative and Gram-positive bacteria - da Silva, Raquel Nunes (2018)
Phthalocyanines bearing four or eight sulfonamide units were synthesized and their efficiency in the photodynamic inactivation of Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria was evaluated. Conjugates with simpler sulfonamide units (N,N-diethylbenzenesulfonamide, N-isopropylbenzenesulfonamide and N-(4-methoxyphenyl)benzenesulfonamide) caused stronger inactivation than those with heterocyclic groups (N-(thiazol-2-yl)benzenesulfonamide) or long alkyl chains (N-dodecylbenzenesulfonamide) in both bacteria. Furthermore, the encapsulation of the phthalocyanine-sulfonamide conjugates within polyvinylpyrrolidone micelles, used as drug delivery vehicles, in general showed to enhance the inactivation efficiency. The results show that encapsulated phthalocyanine-sulfonamide conjugates are a promising class of photosensitizers to be used in photodynamic antimicrobial therapy.